Toward an objective evaluation of teacher performance: The use of variance partitioning analysis, VPA. - Alicias, Eduardo R. (Education Policy Analysis Archives, 2005)
Evaluation of teacher performance is usually done with the use of ratings made by students, peers, and principals or supervisors, and at times, selfratings made by the teachers themselves. The trouble with this practice is that it is obviously subjective, and vulnerable to what Glass and Martinez call the "politics of teacher evaluation," as well as to professional incapacities of the raters. The value-added analysis (VAA) model is one attempt to make evaluation objective and evidenced-based. However, the VAA model'especially that of the Tennessee Value Added Assessment System (TVAAS) developed by William Sanders'appears flawed essentially because it posits the untenable assumption that the gain score of students (value added) is attributable only and only to the teacher(s), ignoring other significant explanators of student achievement like IQ and socio-economic status. Further, the use of the gain score (value-added) as a dependent variable appears hobbled with the validity threat called "statistical regression," as well as the problem of isolating the conflated effects of two or more teachers. The proposed variance partitioning analysis (VPA) model seeks to partition the total variance of the dependent variable (post-test student achievement) into various portions representing: first, the effects attributable to the set of teacher factors; second, effects attributable to the set of control variables the most important of which are IQ of the student, his pretest score on that particular dependent variable, and some measures of his socio-economic status; and third, the unexplained effects/variance. It is not difficult to see that when the second and third quanta of variance are partitioned out of the total variance of the dependent variable, what remains is that attributable to the teacher. Two measures of teacher effect are hereby proposed: the proportional teacher effect and the direct teacher effect.